ЗАМАНАГӨЙ КӨРКЕМ ТӘЛИМДЕ ART-МЕТОДЛАРДАН ПАЙДАЛАНЫЎ ЖОЛЛАРЫ - Уразимова, Т.В.; Исмайлова, А. (SCIENCE and SOCIETY, 2022)
On the basis of the integrated use of the pedagogical potential of various types and means of art, studying the possibility of using the system of art pedagogy, its methods in the educational process, aimed at humanizing the educational environment, optimizing pedagogical interaction, and creative self-realization of subjects of vocational education.
Keywords: art pedagogy; art therapy; methods of art pedagogy; art education; personality